Examining the Influencing Factors of Consumer Purchase Intention toward Fast Food with Health Concerns as a Moderator - Kamalul Ariffin, Shaizatulaqma; Ng, Fifiana; Abdul Mohsin, Ainul Mohsein (Journal of Entrepreneurship, Business and Economics, 2021)
This study aims to investigate the key factors that influence consumers’ intention to purchase fast food. In specific, this study intends to examine the relationship between attitude, subjective norms, perceived behavioural control and consumer purchase intention toward fast food. Additionally, this study also examines health concerns as a moderator between independent variables and consumer purchase intention toward fast food. The data was collected via an online and face-to-face survey amongst the young generation in Malaysia, and quantitative analysis was used to test the hypotheses. A total of 473 respondents who have experienced consuming fast food participated in this survey, and the data was statistically analysed via SPSS/PLS-SEM. The findings of this study show that attitude and subjective norms were found to positively and significantly influence consumer purchase intention toward fast food, while perceived behavioural control was found to be insignificant. The findings of this study also revealed that health concerns weakened the relationship between attitude and consumer purchase intention toward fast food, whereas health concerns strengthen the relationship between subjective norms and consumer purchase intention toward fast food. Meanwhile, health concern has no moderation effect in the relationship between perceived behavioural control and consumer purchase intention toward fast food. This is one of the few studies examining the health concern as a moderator in the study of consumer purchase intention toward fast food in an emerging market such as Malaysia. The findings help fast-food restauranters and marketers in understanding consumer behaviour and could help marketers as well as organisations to effectively adapt these factors in their marketing strategies, especially toward young consumers with a high health concern. Research paper Keywords: Inconspicuous consumption; Triandis model; Theory of Interpersonal Behaviour; Subtle luxury fashion products; purchase intention Reference to this paper should be made as follows: Kamalul Ariffin. S., Ng, F., & Abdul Mohsin, A. M. (2021). Examining the Influencing Factors of Consumer Purchase Intention toward Fast Food with Health Concerns as a Moderator. Journal of Entrepreneurship, Business and Economics , 9 (2), 39–71.